(untitled) (Educação e Pesquisa, 2023)
This article presents reflections on a pedagogical experience with the indigenous theme in a public school in the Federal District. Although the Federal Law 11.645/2008 was promulgated more than a decade ago, establishing the mandatory teaching of Afro-Brazilian and indigenous history and culture in the Brazilian basic education curriculum, its implementation remains a multifactorial problem for the school system. The objective of the research was to address students’ perceptions about indigenous peoples and the challenges faced by teachers participating in the initiative about teaching the contents foreseen in the Law. The inquiry was developed based on the methodological principles of action research. In this sense, it involved the execution of a set of pedagogical interventions in cooperation with teachers of the arts discipline and the observation of the effects of this action in the light of a critical intercultural perspective. The results of this exercise reveal that there is still a strong reproduction of stereotypical images of the Brazilian national imaginary in students’ perceptions about “Indians”. They also show that there are still gaps and superficiality in teacher training and in teaching resources on the subject, even though we currently have a variety of sources produced by indigenous people in different languages. On the other hand, the pedagogical intervention indicates the fertility of the indigenous theme for the diversification of pedagogical practices and the decolonization of curricula, with significant effects on the educational environment of elementary school.